Sustainable development goals in project management: barriers and insights from key sectors in Kazakhstan - Salimbayeva , R.; Akzambekkyzy, A.; Manarbek, G.; Sagyngaliyeva , A. (Journal of Economic Research & Business Administration, 2025)
Sustainable project management plays a pivotal role in achieving Sustainable Development Goals (SDGs) across various sectors. This study focuses on examining project management practices within the healthcare, education, and construction sectors of Kazakhstan. The goal of the study is to identify barriers and propose solutions for improving the management of projects in these sectors. Key tasks include analyzing management practices, evaluating their effectiveness, and exploring pathways for integrating sustainable approaches. The research progressed through several stages: conducting a comprehensive literature review, developing targeted interview questions, and analyzing the responses. Key results indicate that while some programs achieved moderate success, significant barriers remain, including financial constraints, inconsistent practices, and resistance to innovation. The study’s analysis underscores the need for better integration of sustainability principles and enhanced project management frameworks. This research contributes to the field by providing actionable insights into overcoming barriers to sustainable project management. Its practical significance lies in offering recommendations to policymakers, project managers, and stakeholders to improve project implementation and ensure alignment with SDGs. Key words: Sustainable project management, project barriers, sustainable development goals.